2009
DOI: 10.1021/jp811245r
|View full text |Cite
|
Sign up to set email alerts
|

Improving the Quantum Yields of Semiconductor Quantum Dots through Photoenhancement Assisted by Reducing Agents

Abstract: Surface modification of semiconductor quantum dots (QDs) often causes a drastic reduction of photoluminescence quantum yield (QY). Here, we report an efficient way to improve photoluminescence (PL) characteristics of silica-coated QDs using the combination of light-induced PL enhancement (photoenhancement) and the small molecule reducing agent, dithiothreitol (DTT). The photoenhancement process in the absence of a reducing agent is usually accompanied by a blue shift and broadening of the PL spectrum as well a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
37
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 57 publications
(164 reference statements)
0
37
0
Order By: Relevance
“…Despite the tremendous advancements in CQW synthesis 20 26 , spectroscopy 31 32 and theoretical modelling 20 23 , a thorough comprehension of charge trapping and charging is still lacking in the literature and so are reliable guidelines for optimizing their optical performances and environmental stability through suitable surface passivation strategies. Furthermore, understanding the mechanism of surface trapping would allow us to fully exploit the reversible dimming of the photoluminescence (PL) efficiency observed for individual CQWs under vacuum 32 to realize novel ‘reverse luminescence sensors’ that become brighter in the presence of oxygen 33 , in contrast to conventional sensors that rely on photodarkening to detect electron-withdrawing agents 34 35 36 37 . These active analytical tools are of great interest for a wide range of applications, spanning from life sciences 37 to pollution monitoring and aerospace engineering 38 that would strongly benefit from efficient luminescent-sensing varnishes to probe variations of the oxygen level in the atmosphere.…”
mentioning
confidence: 99%
“…Despite the tremendous advancements in CQW synthesis 20 26 , spectroscopy 31 32 and theoretical modelling 20 23 , a thorough comprehension of charge trapping and charging is still lacking in the literature and so are reliable guidelines for optimizing their optical performances and environmental stability through suitable surface passivation strategies. Furthermore, understanding the mechanism of surface trapping would allow us to fully exploit the reversible dimming of the photoluminescence (PL) efficiency observed for individual CQWs under vacuum 32 to realize novel ‘reverse luminescence sensors’ that become brighter in the presence of oxygen 33 , in contrast to conventional sensors that rely on photodarkening to detect electron-withdrawing agents 34 35 36 37 . These active analytical tools are of great interest for a wide range of applications, spanning from life sciences 37 to pollution monitoring and aerospace engineering 38 that would strongly benefit from efficient luminescent-sensing varnishes to probe variations of the oxygen level in the atmosphere.…”
mentioning
confidence: 99%
“…The reaction time is an important key for the formation thickness of silica and affects the quality of the nanoparticles. 15 Figure 5(a) shows photographs of 5 nm ZnO nanoparticles before exposure to UV light and after exposure to UV light. Figure 5(b) shows the absorption and emission spectra of the ZnO particles.…”
Section: Resultsmentioning
confidence: 99%
“…For instance, Peng et al reported that the PL of CdSe nanocrystals is largely increased by forming a CdS shell onto the surface of CdSe NCs via a successive ionic deposition [20]. Alternatively, the photoactivation of luminescent NCs by exposing to light irradiation have also employed to improve the PL-QY of NCs [21][22][23][24][25][26]. Gao et al found that the PL-QY of CdTe NCs in aqueous solution is greatly improved by illuminating the as prepared thioglycolic acid (TGA) stabilized CdTe NCs in N 2 saturated solution [21].…”
Section: Introductionmentioning
confidence: 99%
“…Gao et al found that the PL-QY of CdTe NCs in aqueous solution is greatly improved by illuminating the as prepared thioglycolic acid (TGA) stabilized CdTe NCs in N 2 saturated solution [21]. Park et al found that the PL-QY of silica coated CdSe/ZnS QDs can be efficiently enhanced by irradiating the QDs in the presence of dithiothreitol (DDT) [22]. Very recently, Kim et al reported that the PL of CdSe/CdS/CdZnS/ZnS in polymer matrix was enhanced by irradiating with UV light [23].…”
Section: Introductionmentioning
confidence: 99%